Removal of port-site and pelvic parasitic fibroids after laparoscopic myomectomy with morcellation: a case report and literature review - Wu, Yushi; Dai, Yi; Li, Xiaoyan; Shi, Jinghua; Gu, Zhiyue; Zhang, Chenyu; Yan, Hailan; Leng, Jinhua (Frontiers in Medicine, 2025)
We present the case of a 39-year-old Chinese woman who presented with a palpable mass in her abdominal wall and pelvic cavity 9 years after undergoing laparoscopic myomectomy. Six abdominal wall fibroids, 18 intramural fibroids, 1 posterior adenomyoma, and 6 uterine rectal fibroids were excised. Abdominal wall fibroids were located near the right trocar site of the previous laparoscopic myomectomy, with a total diameter of 15 cm. Histopathologic examination confirmed leiomyoma. Port-site PL is a rare complication caused by power morcellation following laparoscopic surgery. Even rarer are cases involving both the abdominal wall and the pelvic cavity. To reduce the occurrence of port-site PL, it is crucial to prevent tissue dissemination via excessive fragmentation. In addition to exploring and irrigating pelvic and abdominal cavities, diligent efforts should be made to irrigate the trocar-site abdominal wall to prevent tissue implantation. It is recommended that morcellation be performed, whenever feasible, within a containment bag or by conducting intracapsular myomectomy.